Swimming, Doping and Anti-Doping - Ohta-Fukushima, M.; Mutoh, Y.; Suzuki, Y.; Itoh, Y.; Takasugi, S.; Yasuda, K.; Enatsu, A. (Proceedings XII FINA World Congress on sports medicine, April 1997 Göteborg, Sweden, 1997)
Ziel der Studie: